High-performance white organic light-emitting diodes with doping-free device architecture based on the exciton adjusting interfacial exciplex. Issue 21 (30th April 2020) - Ying, Shian; Zhang, Shuai; Yao, Jingwen; Dai, Yanfeng; Sun, Qian; Yang, Dezhi; Qiao, Xianfeng; Chen, Jiangshan; Ma, Dongge
Abstract : A high-performance doping-free three-color WOLED with stable spectrum emission was achieved based on the exciton adjusting interfacial exciplex. Abstract : White organic light-emitting diodes (WOLEDs) with a doping-free device architecture have aroused more attention due to their attractive merits such as simplified fabrication procedures and reduced costs. However, their electroluminescence performance is still very unsatisfactory and needs to be further improved. Here, high-performance doping-free two-color and three-color WOLEDs with accurate manipulation of excitons have been successfully fabricated by optimizing the interfacial exciplex. As a result, two-color WOLEDs exhibit controllable electroluminescence spectra with a wide correlated color temperature (CCT) spanning from 2878 to 9895 K at the voltage of 4 V, as well as the maximum forward-viewing power and current efficiencies of 83.2 lm W −1 and 63.3 cd A −1, respectively. The three-color WOLED not only achieves maximum efficiencies of 50.1 lm W −1 and 44.7 cd A −1, but also exhibits superior color stability with a color rendering index of 86, a CCT of 2679 K, and Commission International de I'Eclairage coordinates of (0.49, 0.46) at a voltage of 5 V. Such surprising efficiencies obtained in our WOLEDs indicate that the reasonable application of the interfacial exciplex should be a helpful way to develop high-performance and low cost WOLEDs using a simple technology.